Distribution of saa gene variants in verocytotoxigenic Escherichia coli isolated from cattle and food - Lucchesi, Paula Maria Alejandra (2006)
The pathogenesis of verocytotoxigenic Escherichia coli (VTEC) infection in humans is multifactorial, given that verocytotoxins are the principal virulence factor. Most strains causing serious diseases possess the eae gene that encodes the adhesin intimin, but its presence is not essential for virulence as some cases are caused by eae-negative strains. An autoagglutinating adhesin designated Saa was found in some eae-negative strains. This protein varies in size as a consequence of variation in the number of copies of a 37-aa repeat unit in the C-terminal region. Based on these findings, we designed PCR primers to amplify the region coding for these differences to detect saa gene variants present in VTEC strains isolated in Argentina from cattle and meat. The gene saa was detected in 36 (31.6%) eae-negative strains and 5 variants were found. Strains isolated from cattle possessed 4 saa variants, whereas 2 variants were present in isolates from meat. Saa variant 1 predominated (18 strains) and was distributed in strains isolated both from cattle and from meat. Our study revealed the existence of two novel saa variants, termed 4 and 5, which have a higher number of 111-bp repeats than saa genes previously studied.